Izba Pamięci Adama Grzymały-Siedleckiego Wojewódzkiej i Miejskiej Biblioteki Publicznej im. dr. W. Bełzy w Bydgoszczy - historia, działalność, zasób, perspektywy (Kronika Bydgoska, 2014)
The Adam Grzymała-Siedlecki Memorial Chamber, situated on 5 Libelta Street, is one of the branches of the Dr. W. Bełza Regional and Municipal Public Library in Bydgoszcz. The patron of the institution, who lived in 1876-1967, was a well-known literary and theater critic, as well as prose writer, playwright, director, screenwriter and publicist. The Chamber was established in 1968, on the exact date of the birth and also death of the writer; a year later, the reading room - Theater Research Studio - was opened as well. The museum features a number of memorabilia, including furniture, personal objects, photographs and pictures, which purpose is popularization of knowledge about the patron through guided tours and organization of cultural events. The library consists of a book collection concerning the study of theatre. Its most valuable items are the books that were once owned by Grzymała-Siedlecki; newspapers, documents of social life (photographs, posters and theater programs) and an extensive collection of manuscripts. The principal function of the Theater Research Studio is making available library collections, performance of a preliminary survey of the library holdings, and organization of exhibitions. The theater archives were damaged during the fire of the Bydgoszcz Municipal Theater in the end of World War II. Due to this reason, materials stored in the Chamber and Studio became one of only several sources making possible research on the history of the Bydgoszcz theater and cultural life in Bydgoszcz during the prewar period.